Femme feral - Beckbessinger, Sam (Penguin Books, 2026)
"Hyper-competent Ellie thinks she's going through perimenopause, but discovers she's actually turning into a werewolf in this feminist, dark-comedy debut. The head of a company she started from the ground-up, the worried mother of a troublingly secretive daughter, and the wife of an easy-going man who always has her picking up the slack-Ellie is already juggling too much. So, it's an inconvenient time to find herself beset by strange physical changes: hair sprouting in new places, running hot, trouble sleeping, losing time, finding bloodstains in all her clothing. And underneath it all, a boiling rage that threatens to disrupt the life she's worked so hard to build. Her doctor diagnoses perimenopause. But it's another twenty-eight-day cycle that's taking hold, one that involves fur, teeth, and a not-insignificant amount of howling at the moon-and that gifts Ellie incredible strength and speed. Her new power's thrilling, as is releasing the anger she's suppressed for years-especially as it turns out that there are some problems that can be solved with violence: The terrible new hire who is sabotaging her careful plans. The creep who's stalking her daughter. Only, the beast within isn't easy to control, and its bloody trail is getting harder to hide. With an obsessive hunter on her trail and a growing fear of what she's becoming, Ellie must find a way to yoke her fury before she tears through the people she loves. A deeply gratifying, highly addictive and provocative read, Femme Feral is an exhilarating expression of feminine rage, with a warning: If you swallow your anger, it's sure to come back with a bite"-- Provided by publisher.